On the gender GAP, ICT and institutional quality: A dynamic panel data analysis - Kucuk, Nezahat (National Academy of Management eco@nam.kiev.ua Vul. Panasa Myrnogo, 26 Kyiv 01011, 2013)
The objective of this study is to examine the relationship between gender gap, information communication technology (ICT), and governance and institutional quality. The study also analyzes how ICT interacts with social and institutional infrastructure to impact gender equality. Using a panel dataset for 209 countries covering the period from 2000 to 2010 and the dynamic panel generalized method of moments estimation (GMM), the paper finds that both ICT and institutional infrastructure have significant positive effect on gender equality. More importantly, simultaneous improvement in ICT and institutional quality exerts an independent influence on gender equality, over and above any influence each of these two variables may separately have. © 2013 Nezahat Kucuk.
Keywords: Gender gap; Ict; Institutional quality; Panel data